The influence of coffee on incremental exercise, recovery and post exercise urine caffeine metabolites' concentrations - Turnagol, H. H.; Guner, R.; Bayer, C.; Cetemen, M.; Acikada, C. (Medicine & Science in Sports & Exercise, 1998)
The effects of regular (5 mg/kg caffeine) and decaffeinated coffee on an incremental bicycle exercise (aerobic work) and recovery were evaluated. Male soccer players (N = 14) were tested under each coffee condition and a no-coffee condition. As well Ss were give the same conditions but without exercise. The exercise was performed in three-minute stages, each successive level being increased by 50 watts, and continued until exhaustion. Caffeine had no effect on test parameters (VO2, VCO2, RER) or recovery. No S exceeded the caffeine limit of 12 ug/ml. Caffeine and caffeine metabolites were similar under the exercise and no exercise conditions. Implication. Ingestion of caffeine (via coffee) does not have a positive effect on aerobic work. This contradicts the general belief that caffeine extends endurance capacity.